2018
DOI: 10.1096/fj.201800014rr
|View full text |Cite
|
Sign up to set email alerts
|

The benzodiazepine anesthetic midazolam prevents hyperglycemia‐induced microvascular leakage in the retinas of diabetic mice

Abstract: We investigated the beneficial effects of midazolam against vascular endothelial growth factor (VEGF)-induced vascular leakage and its molecular mechanism of action in human retinal endothelial cells (HRECs) and the retinas of diabetic mice. Midazolam inhibited VEGF-induced elevation of intracellular Ca, generation of reactive oxygen species (ROS), and transglutaminase activation in HRECs; these effects were reversed by the GABA, type A (GABA) receptor antagonist flumazenil but not by the translocator protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 36 publications
0
39
0
1
Order By: Relevance
“…Supplementation with VEGF may also have affected the ROS production; there was no increase in the extracellular concentration of H 2 O 2 from HRECs in the medium without VEGF, even with 25 mmol/L glucose. VEGF can promote the production of ROS by HRECs (59). Nevertheless, we considered it reasonable to use supplementation with VEGF to mimic the intraocular condition of retinal damage from diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with VEGF may also have affected the ROS production; there was no increase in the extracellular concentration of H 2 O 2 from HRECs in the medium without VEGF, even with 25 mmol/L glucose. VEGF can promote the production of ROS by HRECs (59). Nevertheless, we considered it reasonable to use supplementation with VEGF to mimic the intraocular condition of retinal damage from diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, a vascular permeability factor, plays a key role in DR (Lee et al, 2016). Previously, it was reported that VEGF activates transglutaminase 2 (TGase2) by intracellular Ca 2+ elevation and ROS generation and subsequently induces microvascular leakage through adherens junction disassembly in the retinas of diabetic mice (Lee et al, 2017; Lee et al, 2018). We found that VEGF levels were persistently elevated in the retinas of HGM mice and that dopamine prevented vascular leakage induced by intradermal injection of VEGF into mouse ears.…”
Section: Discussionmentioning
confidence: 99%
“…CP also prevents hyperglycemia‐induced vascular leakage and metastasis of melanoma cells by inhibiting TGase2 in the lungs of diabetic mice (30). TGase2 plays an essential role in hyperglycemia‐induced vascular leakage in the retinas of diabetic mice (24), which was prevented by CP, the benzodiazepine anesthetic midazolam, or cysteamine derived from coenzyme A degradation (27, 36, 37). In the present study, oral administration of Cys inhibited hyperglycemia‐induced TGase2 activation and ROS generation in the aortas of HGM mice.…”
Section: Discussionmentioning
confidence: 99%
“…In situ TGase transamidating activity was determined by confocal microscopy, as previously described in Lee et al . (27). Briefly, cells were incubated with 1 mM 5‐(biotinamido)pentylamine at 37° for 1 h and then fixed and permeabilized.…”
Section: Methodsmentioning
confidence: 99%